Effects of non-medicated and medicated urea molasses multi-nutrient block supplements on nutrient intake and blood mineral profile of lactating Saanen goats - Panadi, Mira; Rusli, Nor Dini; Mohamed, Wan Zahari; Mat, Khairiyah (UMK Press, 2019)
Poor nutrition is a major contributor to the performance of dairy goats on smallholder farms. Hence, strategic supplementation is required to overcome nutritional deficiencies. This paper reviews the effects of urea molasses multi-nutrient block (UMMB) and medicated urea molasses multi-nutrient block (MUMB) supplements in comparison with imported commercial mineral blocks (CMB) on nutrient intake and blood mineral profile of Saanen lactating goats. A 90-day feeding trial was conducted at Yusof Ecofarm, Tanah Merah, Kelantan, Malaysia. Twenty four (24) Saanen lactating goats were assigned to four dietary treatments with six (6) goats in each group based on completely randomized block design. Goats in T1 (control) were fed with basal diet only that comprise of roughages and goat pellet while T2, T3 and T4 received equal amount of basal diet and allowed for ad-libitum licking of UMMB, MUMB and CMB respectively. Total dry matter intake (DMI) (kg/d) were 1.14, 1.29, 1.25 and 1.16 in T1, T2, T3 and T4 respectively whereas the UMMB, MUMB and CMB intakes (g/d) were 86.8, 50.4 and 36.6 respectively. There were significant differences (p<0.05) between treatments on nutrient intake. Crude protein (CP), crude fiber (CF), ether extract (EE), acid detergent fiber (ADF) and neutral detergent fiber (NDF) were significantly higher (p<0.05) in T2 and T3 as compared to T1 and T4. The serum concentrations of calcium (Ca), ferum (Fe), copper (Cu) and zinc (Zn) were significantly higher (p<0.05) in T2 with the values of 33.60 ppm, 341.67 ppb, 270.00 ppb and 138.30 ppb respectively as compared to other treatments. Hence, the findings of this research revealed that both UMMB and MUMB were effective in improving nutrient intake and blood mineral profile of lactating Saanen goats.